RANCANG BANGUN SISTEM INFORMASI OBYEK WISATA DI KOTA BATAM BERBASIS WEB - KIKI VALENTINA SIANTURI; Elisa, Erlin (LPPM Universitas Putera Batam, 2022)
This study aims to design a web-based Batam City tourism information system as a source of information to find out tourist attractions and other wealth in Batam. The tourist attraction information system in Batam City is made with the PHP programming language and the data is stored in a database that uses MYSQL to improve system performance in data storage. Google Maps API is one of the facilities in the design of this information system that can be used to add maps to the website using JavaScript.